Lung water quantification by cardiac magnetic resonance imaging: a novel prognostic tool in hf. (25th November 2020) - Rocha, B.M.L; Lopes Da Cunha, G.J; Freitas, P; Lopes, P; Santos, A.C; Guerreiro, S; Tralhao, A; Ventosa, A; Andrade, M.J; Aguiar, C.M.T; Abecasis, J; Saraiva, C; et al.
Abstract: Background: Cardiac magnetic resonance (CMR) imaging has recently been proposed to quantify lung water density (LWD, %) non-invasively. Given that pulmonary congestion plays a key role in the pathophysiology of Heart Failure (HF), we designed a study to assess the prognostic significance of a simplified LWD measure in patients with HF and reduced left ventricular ejection fraction (LVEF). Methods: We conducted a single-center retrospective study of consecutive patients with HF and LVEF <50% who underwent CMR on a 1.5T scanner. Those with severe interstitial lung disease or chronic liver disease were excluded. All measurements were performed in a parasagittal plane at the right midclavicular line on a standard HASTE sequence, which is widely available in all CMR studies. As previously reported, LWD was determined by the lung-to-liver signal ratio multiplied by 0.7. A cohort of 102 healthy controls was used to derive the upper limit of normal (mean ± 2SD) of the LWD (21.2%). The primary endpoint was a composite of all-cause death or HF hospitalization. Results: A total of 290 HF patients (mean age 64±12 years, 74.8% male, 56.2% of ischemic etiology) with a mean LVEF of 34±10% were included. LWD measurement took on average 35±4 seconds and showed excellent inter-observer agreement (intra-class correlation coefficient >0.90). LWD was increased in 65 (22.4%) patients. Compared to those with normal LWD, the former were more symptomatic (NYHA ≥III: 29.2% vs. 1.8%; p=0.017) and had higher median NT-proBNP [1973 (IQR: 809–3766) vs 802 (IQR: 355–2157pg/mL); p<0.001]. During a median followup of 21 months (IQR: 13–29), 20 (6.9%) patients died and 40 (13.8%) had at least one HF hospitalization. In multivariate analysis, LVEF (HR per 1%: 0.96; CI-95%: 0.93–0.99; p=0.024), creatinine (HR per 1mg/dL: 2.43; CI-95%: 1.25–4.71; p=0.009) and LWD (HR per 1%: 1.06; CI-95%: 1.01–1.12; p=0.013) were independent predictors of the primary endpoint. The findings were mainly driven by an association between LWD and HF hospitalization (HR per 1%: 1.08; CI-95%: 1.03–1.13; p=0.002). Conclusions: A CMR-derived method for LWD quantification independently predicts an increased risk of death or HF hospitalization in HF patients with LVEF <50%. Our results support LWD measurement as a simple, reproducible and widely available method, further adding to the prognostic role of CMR in this population. Funding Acknowledgement: Type of funding source: None